Research Results of a Combined Machine that Increases Productivity in Grain Farming (Global Journal of Science Frontier Research, 2023)
Fertile and nutritious soil is the main condition for increasing the productivity of cereal crops in agriculture By adding mineral fertilizers to the soil nutrients are added to the nutrients in the soil and enrich it by increasing its fertility Even distribution of fertilizers in the field is one of the main conditions that increase its efficiency It is not possible to increase the productivity infinitely by increasing the fertilizer rate Uneven fertilization significantly affects the characteristics of the crop and causes environmental pollution The inhomogeneity of the field in terms of nutrients resulting from fertilization is often the main cause of uneven cropping Cereal plants also cause yield loss which in some years can reach about 25-60 Experience in the operation of modern technical means has shown that at present there is a need to provide an equal amount of fertilizer on the slopes to under the soil fully meeting the agro-technical requirements
Keywords: slope; plow; mineral fertilizer; combined plough; speed